2010
DOI: 10.1186/1471-2229-10-16
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulatory network triggered by oxidative signals configures the early response mechanisms of japonica rice to chilling stress

Abstract: BackgroundThe transcriptional regulatory network involved in low temperature response leading to acclimation has been established in Arabidopsis. In japonica rice, which can only withstand transient exposure to milder cold stress (10°C), an oxidative-mediated network has been proposed to play a key role in configuring early responses and short-term defenses. The components, hierarchical organization and physiological consequences of this network were further dissected by a systems-level approach.ResultsRegulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
160
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(172 citation statements)
references
References 110 publications
(219 reference statements)
10
160
1
1
Order By: Relevance
“…As H 2 O 2 levels increase rapidly upon salt stress (Hong et al, 2009), we propose that the induction of these TF genes is at first regulated by H 2 O 2 -dependent pathways rather than by signaling pathways mediated by ABA. Similarly, during chilling stress, it has been demonstrated that genes induced by oxidative stress are activated earlier than those responsive to ABA (Yun et al, 2010). It is notable that ABA and ROS signaling pathways affect each other through feed-forward and feedback loops.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As H 2 O 2 levels increase rapidly upon salt stress (Hong et al, 2009), we propose that the induction of these TF genes is at first regulated by H 2 O 2 -dependent pathways rather than by signaling pathways mediated by ABA. Similarly, during chilling stress, it has been demonstrated that genes induced by oxidative stress are activated earlier than those responsive to ABA (Yun et al, 2010). It is notable that ABA and ROS signaling pathways affect each other through feed-forward and feedback loops.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the early response regulatory network triggered by oxidative signals is of great importance for the adaptation of rice to cold stress (Cheng et al, 2007). Moreover, genes responding to oxidative stress are activated earlier than those mediated by ABA (Yun et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reversible redox modulation of Cys residues of the proteins is perhaps the most obvious mechanism for the H 2 O 2 -mediated activation of MAPK pathways. Transcriptomic analyses of Arabidopsis plants have revealed hundreds of H 2 O 2 -responsive genes (Ding et al, 2010;Yun et al, 2010). It was shown that H 2 O 2 produced inside the chloroplasts can leave the chloroplasts thus escaping the effective antioxidant systems located inside the chloroplast .…”
Section: Ros As Important Signalling Agentsmentioning
confidence: 99%
“…Sin embargo también se ha encontrado su participación en mecanismos de respuesta a estrés abiótico (Alves et al, 2015;. Ejemplos: estrés por sequía (Davey et al, 2009;Golldack et al, 2011;Ranjan et al, 2012;Yan et al, 2012; ELEMENTOS REGULADORES Bhardwaj et al, 2013;Cao et al, 2013); estrés por temperatura, la cual incluye altas temperaturas, bajas temperaturas y congelación (Rensink et al, 2005;Lim et al, 2006;Bedon et al, 2010;Yun et al, 2010;Jiang et al, 2013;Tian et al, 2013); estrés por metales, como el hierro (Colangelo y Guerinot, 2004;Palmer et al, 2013) y el aluminio (Zeng et al, 2012;Yang et al, 2012b); y estrés por luz (Stracke et al, 2010;Rius et al, 2012), entre otros.…”
Section: Factores De Transcripción Mybunclassified